THE EPISTEMOLOGY OF ISLAM NUSANTARA JURISPRUDENCE AND ITS CONTRIBUTION IN FAMILY LAW REFORM IN INDONESIA - Fuad, Moh. Fahimul; Mukri, Moh.; Alamsyah, A.; Akla, A. (Universitas Islam Negeri Raden Intan Lampung, 2021)
The term Islam Nusantara has sparked and caused polemics, pros, and cons that are quite warm in Indonesia since 2015 until now. As happened in the West Sumatra MUI environment. Islam Nusantara is interpreted as a religious pattern that exists in the archipelago, both at the level of religious practice and how to preach it. The level of amaliyah is interpreted as religious behavior that exists in the archipelago, especially in relation to fiqh which originates from its religious understanding. The problem is: What is the source of knowledge used in formulating Islamic fiqh in Nusantara? What is the validity and method of understanding the sources of knowledge used in formulating Islamic jurisprudence in Nusantara? How is the contribution of Islam Nusantara jurisprudence in reforming family law in Indonesia? This study aims to find answers to the epistemological formulation of Islamic jurisprudence in the archipelago and its contribution to reforming family law in Indonesia. To answer the questions above, the author uses qualitative research methods, types of literature research, the theory of ijtihad with the ushul fiqh approach. This means that the study of the concept of Islam Nusantara is carried out using the framework of ushul fiqh knowledge, especially regarding the concept of ijtihad. At the level of research work, the stretching of thinking to produce fiqh concepts that are unique to the archipelago is seen as part of ijtihad activities. The findings of the research are: (a) The source of knowledge used in formulating Islamic jurisprudence in the archipelago is a source of knowledge commonly known in the study of fiqh and ushul fiqh, both the mujma ’alaih and the mukhtalaf fih, (b) the source of knowledge as said to be valid. By giving a large enough portion to 'urf, and a benefit-oriented understanding, (c) Islam Nusantara’s fiqh can be used as an alternative law in the context of reforming family law in Indonesia.Keywords: Islam Nusantara, Jurisprudence, Epistemology, Legal Reform